The North Borneo Iranun’s Community’s Ethnomedicine Knowledge on Marsh Clam (Geloina expansa) - Diana Demiyah Mohd Hamdan; Jalihah Md Shah; Faizah Gumpulan; Jurry Foo; Khamisah Awang Lukman (2020)
Hamdan DDM, Shah JMD, Gumpulan F, Foo J, Lukman KA. 2020. The North Borneo Iranun's Community's Ethnomedicine Knowledge on Marsh Clam (Geloina expansa). Biodiversitas 21: 30-38. North Borneo is rich with natural resources that have boundless potentials for pharmaceutical product discovery that can lead to socioeconomic development in rural areas as suppliers. Even though rich with cultural heritage and comprises of hundred sub-ethnic groups, detail documentation of ethnomedicinal knowledge in North Borneo from different ethnic groups is still limited and could disappear in no time. The ethnomedicinal knowledge of marsh clam (Geloina expansa) use in the Iranun community (respondents no.=28) living in Kampung Rampayan Ulu, Kota Belud in North Borneo were investigated and the concentration of iron, zinc and copper in different parts of marsh clam tissues were determined. In postnatal care of the Iranun community, many believe that marsh clam soup help boost nursing mother milk supply. Marsh clam is rich with micronutrients of iron followed by zinc and copper. The mantle organ has a higher iron concentration than other tissues. The traditional knowledge to heal blood clotting and bruises is topical application of marsh clam mantle organs onto the wound areas. Although participants have ethnomedicinal knowledge on marsh clam, they have poor knowledge of the nutritional benefits of this clam. Lifelong learning of the benefit of marsh clam is necessary from local health care.